The Relationship Between Urinary Tract Infection And Hyperuricemia Among Children In Tikrit Teaching Hospital - Mohammed A.Younis; Ahmed H. Alanee; Amina H. Alobaidy; Zaid Y. Radeef (Tikrit Journal of Pure Science, 2023)
The current study represents an observational, cross-sectional study by using a simple random sampling technique which included one hundred children patients with UTI from the age of 4-14 years old in Tikrit Teaching Hospital from the first of March 2014 to the end of  May 2014 to find the relationship between UTI and Hyperuricemia in children. The study demonstrates that the prevalence of UTI was common in females (64%) than males (36%) with 2:1 ratio. Also high prevalence of UTI was common in rural area (78%) than urban area (22%) of the total cases, and UTI was common in the patients with low socio-economic state (69%). Prevalence of hyperuricemia among patients with UTI was (27%) of the total cases. The study concluded that the prevalence of UTI was high among children in Tikrit Teaching Hospital and there is a significant association between UTI and Hyperuricemia .